2016
DOI: 10.1371/journal.pone.0153118
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the MMP/TIMP Imbalance and Collagen Production Induced by IL-1β or TNF-α Release from Human Hepatic Stellate Cells

Abstract: Inflammation has an important role in the development of liver fibrosis in general and the activation of hepatic stellate cells (HSCs) in particular. It is known that HSCs are themselves able to produce cytokines and chemokines, and that this production may be a key event in the initiation of fibrogenesis. However, the direct involvement of cytokines and chemokines in HSC (self-)activation remains uncertain. In this study, the effects of pro-inflammatory cytokines IL-1α and β, TNF-α, and IL-8 on the activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
91
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 51 publications
10
91
0
Order By: Relevance
“…Activated HSCs lead to liver metabolism reprogramming, increased autophagy and serious damage to parenchymal cells. This results in loss of the retinoids and enhanced contractility in HSCs, which releases growth factors and inflammatory signal factors in the liver microenvironment, liberates large amounts of extracellular matrix (ECM), and lead to an imbalance of matrix metalloproteinases (MMPs) and matrix inhibitor of metalloproteinase (TIMPs) (Lee et al, ; Robert, Gicquel, Bodin, Lagente, & Boichot, ). HCs and KCs also play an important role in liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Activated HSCs lead to liver metabolism reprogramming, increased autophagy and serious damage to parenchymal cells. This results in loss of the retinoids and enhanced contractility in HSCs, which releases growth factors and inflammatory signal factors in the liver microenvironment, liberates large amounts of extracellular matrix (ECM), and lead to an imbalance of matrix metalloproteinases (MMPs) and matrix inhibitor of metalloproteinase (TIMPs) (Lee et al, ; Robert, Gicquel, Bodin, Lagente, & Boichot, ). HCs and KCs also play an important role in liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The potent proinflammatory cytokine TNF‐α is released by HSCs in response to the profibrogenic mediator TGF‐β. It initiates inflammatory responses through stimulating secretion of other proinflammatory cytokines, such as IL‐1β …”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that IL-17 alone had a very weak or no effect on collagen type I α1 and TIMP1 expression [15]. In addition, in LX-2 cells, TNF-α stimulation up-regulated MMP1, MMP3 and MMP9 expression, whereas collagen type I α1, TIMP1 and MMP2 expressions were unchanged [24,25]. In addition, in LX-2 cells, TNF-α stimulation up-regulated MMP1, MMP3 and MMP9 expression, whereas collagen type I α1, TIMP1 and MMP2 expressions were unchanged [24,25].…”
Section: Discussionmentioning
confidence: 99%